Depositional model of the Ipixuna Formation (Late Cretaceous-?Early Tertiary), Rio Capim area, northern Brazil - Antônio Emídio de Araújo Santos Jr.; Dilce de Fátima Rossetti (Latin American Journal of Sedimentology and Basin Analysis, 2006)
Exposures along open quarries located in the eastern Cametá Sub-Basin provide an opportunity of further discussing the depositional environments of the Upper Cretaceous-?Lower Tertiary Ipixuna Formation. The lower part of this unit emphasized herein, known as the "soft kaolin", consists mostly of kaolinitized sandstones and mudstones with well preserved sedimentary structures that are particularly favorable for facies analysis and paleoenvironmental reconstructions. The sandstones are chiefly cross-stratified, typically with low angle, locally reverse orientated foresets with reactivation surfaces and/or mud drapes. These characteristics, together with a trace fossil assemblage consisting of Ophiomorpha, Thalassinoides, Planolites, Teichichnus, Taenidium and Skolithos, conform to deposition in a coastal setting influenced by tidal processes. Although a previous study has documented tidal processes during deposition of the soft kaolin (Santos Jr. and Rossetti, 2003), this paper shows that the influence of tidal currents was much more important than initially proposed. Hence, the kaolinitized deposits are attributed to tidally influenced fluvial channel (Facies Association A), tidal channel (Facies Association B), tidal flat/mangrove (Facies Association C), and tidal sandy bar/tidal sandy flat (Facies Association D), all together comprising a tide-dominated estuarine system. Exposições ao longo de minas localizadas no leste da Sub-Bacia de Cameá fornecem uma oportunidade única para a condução de discussões focalizando os ambientes deposicionais da Formação Ipixuna (Neocretáceo-?Eoterciário). A porção inferior desta unidade, conhecida como "caulim soft", enfatizada neste trabalho, consiste principalmente em arenitos e argilitos caulinitizados que, por serem bem estratificados, favorecem a análise faciológica visando-se reconstruções paleoambientais. Os arenitos são principalmente estratificados cruzados, tipicamente com foresets de baixo ângulo e, localmente, orientados bidirecionalmente, além de formarem pacotes definidos por superfícies de reativação/ou filmes de argila. Estas características, juntamente com a assembléia de traços fósseis consistindo em Ophiomorpha, Thalassinoides, Planolites, Teichichnus, Taenidium e Skolithos, são consistentes com deposição em ambiente costeiro dominado por correntes de maré. Embora estudo prévio já tenha documentado a influência de correntes de maré durante a deposição da unidade correspondente ao caulim soft, o presente trabalho mostra que esta influência foi muito mais importante do que inicialmente proposto. Assim, os depósitos caulinitizados estudados são produtos de deposição em ambientes de canal de maré com influência fluvial (associação de fácies A), canal de maré (associação de fácies B), planície de maré/mangue (associação de fáices C), e barra/planície de areia dominada por maré (associação de fácies D), tipificando sistema estuarino dominado por maré.